Design and Implementation of an IoT-Based Farmland Monitoring System - Thomas Kunnumpurathu, Sujith; Mary Wilson, Hannah; J Kuriakose, Tom (Journal of Electronic Design Engineering, 2023)
In this paper, we present an innovative design and implementation of an IoT-based farmland monitoring system. The system aims to help farmers with real-time data collection, enabling them to optimize resource utilization and enhance crop yield. By incorporating multiple sensor modules that monitor essential environmental variables such as temperature, moisture, light, and motion, our system provides comprehensive data collection from the whole coverage of the farmland. The sensor modules are meticulously crafted around a powerful PIC16F876A microcontroller and an ESP8266 module, ensuring seamless IoT connectivity. The system operates by consistently reading the sensor modules and transmitting the gathered data to a cloud server at predefined intervals. This data can be used for advanced analysis, generating valuable insights and actionable information for farmers. For instance, the system can identify specific areas of the farm that require immediate attention, empowering farmers to make informed decisions regarding resource allocation and crop management. One of the remarkable features of our system is its scalability, which allows for deployment across vast expanses of farmland, ensuring comprehensive monitoring capabilities. By providing farmers with real-time information about environmental conditions, our system enables proactive measures to be taken, maximizing crop yields, and fostering sustainable agricultural practices. This captivating design exemplifies the tremendous potential of IoT in enabling data-driven decision-making in agriculture. The successful integration of hardware, software, and IoT technologies in implementing our farmland monitoring system showcases a reliable and robust solution for data collection in agricultural settings. With its user-friendly interface and compelling functionality, our system paves the way for a new era of smart farming and sustainable agriculture.